2018
DOI: 10.1158/1541-7786.mcr-18-0410
|View full text |Cite
|
Sign up to set email alerts
|

Taxol Induces Brk-dependent Prosurvival Phenotypes in TNBC Cells through an AhR/GR/HIF–driven Signaling Axis

Abstract: The metastatic cascade is a complex process that requires cancer cells to survive despite conditions of high physiologic stress. Previously, cooperation between the glucocorticoid receptor (GR) and hypoxia-inducible factors (HIF) was reported as a point of convergence for host and cellular stress signaling. These studies indicated p38 MAPK-dependent phosphorylation of GR on Ser134 and subsequent p-GR/HIF-dependent induction of breast tumor kinase (PTK6/Brk), as a mediator of aggressive cancer phenotypes. Herei… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 49 publications
(75 reference statements)
0
24
0
Order By: Relevance
“…We observed similarities in gene expression, cell metabolism, and sensitivity to inhibitors of PELP1 binding partners in endocrine and chemotherapy resistant ER+ cell lines. Although PELP1 expression contributes to cell survival in response to Taxol in TNBC (14), our studies are the first to demonstrate enhanced Taxol tolerance in the context of cyto PELP1 in ER+ breast cancer. Our results in TaxR models highlight the impact of targeting PELP1 binding partners involved in PELP1-mediated CSC self-renewal (Figure 4).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…We observed similarities in gene expression, cell metabolism, and sensitivity to inhibitors of PELP1 binding partners in endocrine and chemotherapy resistant ER+ cell lines. Although PELP1 expression contributes to cell survival in response to Taxol in TNBC (14), our studies are the first to demonstrate enhanced Taxol tolerance in the context of cyto PELP1 in ER+ breast cancer. Our results in TaxR models highlight the impact of targeting PELP1 binding partners involved in PELP1-mediated CSC self-renewal (Figure 4).…”
Section: Discussionmentioning
confidence: 66%
“…Paclitaxel (Taxol) is a chemotherapy used to treat late stage breast cancer. Increased PELP1, HIF1α, and HIF-2α expression has been observed in triple negative breast cancer (TNBC) cells in response to Taxol (14). To evaluate whether PELP1 expression affects response to Taxol in ER+ breast cancer, we treated MCF-7 PELP1 cells (LXSN, WT PELP1, cyto PELP1) cultured as tumorspheres with Taxol (0 to 125 nM).…”
Section: Targeting Pelp1/src-3 Complexes In Therapy Resistant Cell Linesmentioning
confidence: 99%
“…However, activation of GR also promotes cell survival in a variety of epithelial cell types, including in breast cancer models. In studies of TNBC, liganddependent and ligand-independent GR activation have been shown to promote expression of pro-survival proteins (Wu et al 2004, Regan Anderson et al 2018. For example, GR promotes breast tumor kinase (Brk/PTK6) expression in response to dexamethasone (liganddependent), and also in response to hypoxia, cell stress induced by chemotherapy, and anoikis (ligandindependent).…”
Section: Gr Promotes Triple Negative Breast Cancer Cell Survival Migmentioning
confidence: 99%
“…For example, GR promotes breast tumor kinase (Brk/PTK6) expression in response to dexamethasone (liganddependent), and also in response to hypoxia, cell stress induced by chemotherapy, and anoikis (ligandindependent). In TNBC models, hypoxia, paclitaxel, 5-FU, and non-adherent culture all led to p38-MAPKdependent GR Ser134 phosphorylation and ligandindependent activation of gene programs implicated in cellular stress-response (Regan Anderson et al 2016Anderson et al , 2018. GR-dependent Brk/PTK6 induction protected cells from chemotherapy-induced cell death and promoted cell migration (Regan Anderson et al 2018).…”
Section: Gr Promotes Triple Negative Breast Cancer Cell Survival Migmentioning
confidence: 99%
See 1 more Smart Citation